The Berenstain Bears and the good deed - Berenstain, Stan, 1923-; Berenstain, Jan, 1923- (Westport, Conn. : Reader's Digest Kids, 1993)
Papa Bear takes his Bear Scouts off to find someone to do a good deed for to earn their merit badges, but no matter where they look noone needs help.
Keywords: Bears -- Fiction; Scouting -- Fiction